SP4.2.6 Colorectal cancer services during COVID-19; an experience of a tertiary centre. (28th October 2021) - Shang, E; Hamer, N; Jha, T; Abu Talib, M; Garg, D; Jha, M
Abstract: Aims: COVID19 has placed unprecedented constraints on healthcare services. Colorectal cancer (CRC) care was one of the many areas predicted to suffer due to these additional pressures. We believe that despite the challenges posed by COVID19, we have continued to deliver a standard of care for elective and emergency CRC resection that compares favorably with the national average. Method: We conducted an analysis of the elective and emergency CRC resections carried out at a tertiary center over a 10-month period (Feb-Dec 2020). Data was collated from patient, operative, and theatre records and compared to the national average as defined by the 2020 National Bowel Cancer Audit (NBOCA). Results: A total of 227 patients underwent surgery (189 elective and 38 emergencies), with a median age of 69. Of these, 153 were laparoscopic (67%), 57 open (27%), and 17 robotic (7%). The median length of stay was less than the national average; 5 days for elective surgery (NBOCA: 6) and 8 days for emergencies (NBOCA: 10). Within 30 days, overall unplanned readmissions rate was 6.5% (NBOCA: 11.6%) and return to theatre was 3.2% (NBOCA: 8.4%). Elective surgery had a 90-day mortality of 1% (NBOCA: 3%) compared to 7.8% for emergencies (NBOCA: 10.5%). Conclusion: Despite the added constraints of the COVID19 pandemic, CRC resection in our unit remains safe with better outcomes than the national standard. We have demonstrated that with adequate precaution and a concerted team effort, delivery of safe care with reasonable outcome is achievable.